Electronic News Gathering (Eng) Style in The Production of Dabdap Putih Village’s Profile Video - I Made Denny Chrisna Putra; Nyoman Lia Susanthi; I Nyoman Payuyasa; Made Rai Budaya Bumiarta; Ida Bagus Hari Kayana Putra; Gangga Lawranta; Ketut Hery Budiyana (Institut Seni Indonesia Denpasar, 2023)
This research focuses on analyzing the process of creating a profile video of Dabdap Putih Village with the application of the Electronic News Gathering (ENG style) concept as part of village branding efforts. The background of the study illustrates the change of village name from Dapdap Putih to Tista, which is considered to have a negative impact on the community's economy. In response, on January 1, 2023, the name of the village was re-inaugurated as Dapdap Putih, requiring an effective information medium to disseminate this change. The research method used is qualitative with data collection through literature studies, in-depth interviews with related parties, direct observation at profile video production sites, and electronic and non-electronic media documentation. The research analysis refers to the concept of ENG style by utilizing film production management theory and process management. The results of the analysis show that the use of ENG mode in making profile videos provides speed, flexibility in editing, and effective mobility. The production process of the Dabdap Putih Village profile video consists of three stages, namely pre-production, production, and post-production. In production management, five management process frameworks are applied: planning, organizing, staffing, leading, and controlling. In conclusion, the use of modern media technology such as village profile videos with an ENG style approach can be an effective village branding tool. With the involvement of a skilled production team, the use of this technique can increase efficiency in disseminating information and promoting village name changes, as well as showing the best characteristics of the village to the wider community.